Electrocardiographic ST elevation (mosque sign) without myocardial ischemia in an infant with tuberous sclerosis - Alp, Hayrullah; Baysal, Tamer; Karaarslan, Sevim; Alpınar, Abdullah; Çaksen, Hüseyin (Journal of Pediatric Neurology, 2014)
Rhabdomyomas, the most common primary cardiac tumors seen in infants and children, are often associated with tuberous sclerosis. However, these cardiac rhabdomyomas may cause hemodynamic disturbances and arrhythmias. In the present case, we demonstrated an infant with electrocardiographic ST elevation suggesting myocardial ischemia associated with multiple cardiac rhabdomyomas.
Keywords: Rhabdomyoma; tuberous sclerosis; myocardial ischemia; mosque sign; ST segment elevation; infant